STORMPAY PAVEMENT USING DIFFERENT WHEEL LOADS - Elsa Eka, Putri; Liew, S. C.; Mohammad Abdul, Mannan; Ron Aldrino, Chan@Ron Buking; Larry, Silas Tirau (GEOMATE International Society, 2022)
Distress models are required during design to ensure the pavement have a longer service life that is conducted for different axle weight. This research addresses by modeling and analyzing StormPav pavement under various wheel loads to ensure pavement structures can withstand these loads. StormPav pavement is made up of precast concrete with Grade 50, which is also known as the innovative IBS Green Pavement, which has a combination of structural, environmental and economic advantages. The analysis of mechanistic behavior for different structures of pavements and mechanistic behavior of precast StormPav pavements using different wheel loads. WinJULEA and KENPAVE are software used for this research for modeling the real scenario to obtain the deflection, stress, strain and stress of each layer of pavement. It is found that total ESAL increases when there is a heavier truck acting on top of the pavement, and precast StormPav pavement receives the lowest total ESAL compared to flexible and rigid pavement. Among various types of pavements, precast StormPav has lesser maximum deflection, which had 65.11% lesser compared to the flexible pavement due to its largest elastic modulus. Besides, when there is loading from a 24-tonne truck acting on top of the precast StormPav pavement, total deflection is 0.761mm and increases 0.064mm (8.345%) when there is loading change to 26-tonne truck, as precast StormPav pavement is made up of concrete grade 50, which can resist to heavier loading. Precast StormPav pavements have the highest maximum allowable load repetitions to prevent fatigue cracking due to their increased flexural strength, which enables them to withstand greater stresses above the structure. As a result, it can be concluded that precast StormPav pavement is a viable alternative to the pavement because it requires less time for construction and sustains less damage when subjected to heavier loads.